Hydraulic Interactions between Injection Events Using Multiple Injection Strategies and a Solenoid Diesel Injector - Simón Martínez-Martínez; Oscar A. de la Garza; Miguel García-Yera; Ricardo Martínez-Carrillo; Fausto A. Sánchez-Cruz (Energies, 2021)
An experimental study was performed to explore the influence of dwell time on the hydraulic interactions between injection events using pilot injection strategy, split injection strategy, post injection strategy and a solenoid diesel injector. To do so, a sweep of dwell time from 0.55 up to 2 ms using all multiple injection strategies and levels of rail pressure, of 80, 100 and 120 MPa, and single level of back pressure, of 5 MPa, was performed. The hydraulic interactions between injection events were characterized through the second injection hydraulic delay and second injection mass in an injection discharge curve indicator equipped with all the components required for its operation and control. In order to define the operating conditions of the multiple injection strategies, to ensure the same injected fuel mass in all cases, the characteristic curves of injection rate for the solenoid diesel injector studied were obtained. The second injection hydraulic delay increases with dwell time values in the range of 0.55–0.9 ms for all multiple injection strategies and levels of rail pressure tested. Conversely, the second injection hydraulic delay decreases with dwell time values higher than 0.9 ms. Moreover, the second hydraulic delay depends mainly on the dwell time and not on the injected fuel mass during the first injection event. The second injection mass increases with dwell values less than 0.6 ms. By contrast, the second injection mass is not significantly affected by that of the first injection at a dwell time higher than 0.6 ms.